Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Treat the matrices on the right side of each equation like you would a constant.
Let 2X + Y = A and 3X - 4Y = B.
Then you can eliminate Y by taking the sum
4A + B = 4 (2X + Y) + (3X - 4Y) = 11X
==> X = (4A + B)/11
Similarly, you can eliminate X by using
-3A + 2B = -3 (2X + Y) + 2 (3X - 4Y) = -11Y
==> Y = (3A - 2B)/11
It follows that
[tex]X=\dfrac4{11}\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\dfrac1{11}\begin{bmatrix}7&-10\\-7&11\end{bmatrix} \\\\ X=\dfrac1{11}\left(4\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\left(\begin{bmatrix}48&-12\\40&88\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\begin{bmatrix}55&-22\\33&99\end{bmatrix} \\\\ X=\begin{bmatrix}5&-2\\3&9\end{bmatrix}[/tex]
Similarly, you would find
[tex]Y=\begin{bmatrix}2&1\\4&4\end{bmatrix}[/tex]
You can solve the second system in the same fashion. You would end up with
[tex]P=\begin{bmatrix}2&-3\\0&1\end{bmatrix} \text{ and } Q=\begin{bmatrix}1&2\\3&-1\end{bmatrix}[/tex]
Step-by-step explanation:
hence it has been done . check the file .
hope this helped you
any problem then comment it .
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.